2017
DOI: 10.1039/c7ra01006k
|View full text |Cite
|
Sign up to set email alerts
|

Indolylbenzothiadiazoles with varying substituents on the indole ring: a systematic study on the self-recovering mechanochromic luminescence

Abstract: A series of mechanochromic fluorophores exhibited self-recovering mechanochromic luminescence properties with varying emission color and recovery times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…1, top). 25,26 Thus, in this work we wanted to explore their utility as imaging agents for uorescent cell microscopy and also study how different N-substituents on the indole motif affect the photophysical properties (Fig. 1, bottom).…”
Section: Resultsmentioning
confidence: 99%
“…1, top). 25,26 Thus, in this work we wanted to explore their utility as imaging agents for uorescent cell microscopy and also study how different N-substituents on the indole motif affect the photophysical properties (Fig. 1, bottom).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, 3-alkyl-substituted derivatives exhibited self-recovering MCL, and recovery time of this MCL could be controlled by the substituents. 19,20 For example, the ground samples of N-methyl-substituted 10d quickly recovered to the original state within 10 s, whereas N-benzoyl-substituted 10b required 2 h. Differential scanning calorimetry (DSC) analysis suggested that the relatively high glass-transition temperature above room temperature might be the origin of longer recovery times. Compared with the non-MCL dye 10e, 3-methylsubstituted 10a exhibited slipped antiparallel stacks of benzothiadiazole rings.…”
Section: Organic Crystalline Compounds With Various MCL Propertiesmentioning
confidence: 99%
“…Based on the molecular design principle of indolylbenzothiadiazoles 10, 19,20 the author and coworkers developed novel donor-acceptor-type MCL compounds 17 by using phenanthroimidazole ring as the electron-donating heteroaromatic group in 2019 (Figure 4d). 32 Compounds 17af were highly emissive both in toluene and in the crystalline state, and exhibited bathochromically shifted MCL except for methoxy-substituted derivative 17c.…”
Section: Directional Control Of Luminescence Wavelengthmentioning
confidence: 99%
“…Mechanofluorochromic materials as a kind of “smart material’’ have its potential applications in mechanosensors, fluorescence switches, and data storage so on [17,18,19,20,21,22,23,24,25,26]. Recently, rationally controlling the design of molecular mechanofluorochromic behavior is still a huge challenging, two main problems restrict the development of this kind of materials: the lack of deep understanding for the structure-property relationship of such materials and the fluorescent quenching effect in the solid state [27,28,29,30,31]. It is exciting that a major breakthrough came from an unusual aggregation-induced emission (AIE) phenomenon in the study of 1-methyl-1,2,3,4,5-pentaphenylsilole [32].…”
Section: Introductionmentioning
confidence: 99%